2015
DOI: 10.1074/jbc.m114.594028
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Endoplasmic Reticulum (ER) Stress and the MEK/ERK Pathway Potentiates Apoptosis in Human Triple Negative Breast Carcinoma Cells

Abstract: Background: Triple negative breast cancers (TNBC) are resistant to conventional therapies and molecular targets of TNBC are not explored in detail. Results: Coupling of ER stress and the MEK/ERK pathway by nifetepimine effectively kills TNBC cells. Conclusion: Nifetepimine plays a significant role in inducing apoptosis in TNBC cells. Significance: Our findings strongly suggest that nifetepimine may act as a potent anti-cancer agent for treatment of TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It has been identified that upregulation of ER stress may induce apoptosis of cancer cells ( 41 , 42 ). ER stress upregulation potentiating apoptosis also has been observed in human triple negative breast carcinoma cells ( 43 ). In the present study, it has been demonstrated that ATF6, IER1 RERK, and CHOP expression levels were increased by synergetic treatment of I-131 and LEB in NPC cells and tumor tissues.…”
Section: Discussionmentioning
confidence: 84%
“…It has been identified that upregulation of ER stress may induce apoptosis of cancer cells ( 41 , 42 ). ER stress upregulation potentiating apoptosis also has been observed in human triple negative breast carcinoma cells ( 43 ). In the present study, it has been demonstrated that ATF6, IER1 RERK, and CHOP expression levels were increased by synergetic treatment of I-131 and LEB in NPC cells and tumor tissues.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, the Erk1/2 (p42/44) kinases were induced only at moderate doses of Tm, with peak activation being observed at 20-50 nM. Erk1/2 signaling has been associated with ER stress in prior studies and in some cases has been shown to serve a pro-survival or autophagyinducing role in the cellular response (Arai et al 2004;Jiang et al 2007;Ghosh et al 2015). Inhibition of the MEK/ERK pathway was recently shown to dramatically increase apoptosis activation in breast cancer cells experiencing ER stress (Ghosh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Erk1/2 signaling has been associated with ER stress in prior studies and in some cases has been shown to serve a pro-survival or autophagyinducing role in the cellular response (Arai et al 2004;Jiang et al 2007;Ghosh et al 2015). Inhibition of the MEK/ERK pathway was recently shown to dramatically increase apoptosis activation in breast cancer cells experiencing ER stress (Ghosh et al 2015). The restriction of Erk1/2 signaling to lower doses of Tm in our study may identify an important protective measure induced by cells during adaptation to survivable levels of ER dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that TNBC cells may be more vulnerable to CHOP activation than cells that are not known for the XBP1 activation (such as estrogen receptor positive adenocarcinoma cell line MCF7). 22, 23 To test this idea, we compared the viabilities of HCC-1086 cells and MCF7 cells treated with 3d . As shown in Figure 3D, treatment of 3d caused the death in both cell lines in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%